Effects of environmental conditions on reproductive effort and nest success of Arctic‐breeding shorebirds. (26th January 2018) - Weiser, Emily L.; Brown, Stephen C.; Lanctot, Richard B.; Gates, H. River; Abraham, Kenneth F.; Bentzen, Rebecca L.; Bêty, Joël; Boldenow, Megan L.; Brook, Rodney W.; Donnelly, Tyrone F.; English, Willow B.; Flemming, Scott A.; et al.
Abstract : The Arctic is experiencing rapidly warming conditions, increasing predator abundance, and diminishing population cycles of keystone species such as lemmings. However, it is still not known how many Arctic animals will respond to a changing climate with altered trophic interactions. We studied clutch size, incubation duration and nest survival of 17 taxa of Arctic‐breeding shorebirds at 16 field sites over 7 years. We predicted that physiological benefits of higher temperatures and earlier snowmelt would increase reproductive effort and nest survival, and we expected increasing predator abundance and decreasing abundance of alternative prey (arvicoline rodents) to have a negative effect on reproduction. Although we observed wide ranges of conditions during our study, we found no effects of covariates on reproductive traits in 12 of 17 taxa. In the remaining taxa, most relationships agreed with our predictions. Earlier snowmelt increased the probability of laying a full clutch from 0.61 to 0.91 for Western Sandpipers, and shortened incubation by 1.42 days for arcticola Dunlin and 0.77 days for Red Phalaropes. Higher temperatures increased the probability of a full clutch from 0.60 to 0.93 for Western Sandpipers and from 0.76 to 0.97 for Red‐necked Phalaropes, and increased daily nest survival rates from 0.9634 to 0.9890 for Semipalmated Sandpipers and 0.9546 to 0.9880 for Western Sandpipers. Higher abundance of predators (foxes) reduced daily nest survival rates only in Western Sandpipers (0.9821–0.9031). In contrast to our predictions, the probability of a full clutch was lowest (0.83) for Semipalmated Sandpipers at moderate abundance of alternative prey, rather than low abundance (0.90). Our findings suggest that in the short‐term, climate warming may have neutral or positive effects on the nesting cycle of most Arctic‐breeding shorebirds.